Microfinance in the Brahmaputra-Jamuna chars: the context, the providers and way forward - Marin, Imran; Hassan, M. Emrul; Maniruzzaman, Md. (BRAC, 2019)
Informal financial sources dominate the financial landscape of the char areas in ways distinct from the mainland areas of rural Bangladesh. Microfinance in the char areas has not even scratched the surface of the first and basic microfinance challenge - outreach. However, the challenges of expanding outreach and developing innovative products and delivery mechanisms go hand is hand in the char areas, in a way that is distinct from the general mainland rural Bangladesh. This is because investments in a core product and methodology experimentation that works, for the most part, in mainland rural Bangladesh w<1s already undertaken by Grameen and other microfinance pioneers, such as BRAC and ASA. This is not the case for the char areas. Good microfinancing in the char areas would involve significant investment in building knowledge and capacity. High chances of selection and frequent seasonal migration are two important features of char dwellers' livelihood. Incomings into the household is usually much less regular than it is on the mainland and a large proportion of income come in lumps from seasonal migration. Livestock earning is the most regular among the common sources from which char dwellers derive their income. However, poor price, lack of timely and cost effective veterinary sen·ices, livestock fodder and safety problems during flood periods, etc. pose significant challenges to this important sector for the char dwellers. Opportunities to engage in activities that will smoothen the income flow is restricted by difficulties of market access and general decline in the adjoining mainland....